2017
DOI: 10.1177/2332649216683966
|View full text |Cite
|
Sign up to set email alerts
|

Tableside Justice: Racial Differences in Retributive Reactions to Dissatisfaction

Abstract: Existing evidence indicates that racial discrimination is a common, if not pervasive, feature of Black Americans’ experiences in U.S. consumer markets. However, few studies have quantitatively explored specific social psychological and interactional consequences of consumer racial discrimination. In response, we draw from literatures on experiences, attributions, and reactions to racial discrimination to posit and test for Black-White differences in consumers’ behavioral responses to dissatisfactory dining exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 58 publications
1
8
0
Order By: Relevance
“…Under automatic gratuities, servers may be less concerned about delaying food for Black patrons. This cost-based explanation aligns with Brewster and Brauer's (2017) finding that black patrons were more likely to penalize servers through tipping when dissatisfied with service, and with which found that Black patrons rated their servers less prompt, controlling for objective service cues.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Under automatic gratuities, servers may be less concerned about delaying food for Black patrons. This cost-based explanation aligns with Brewster and Brauer's (2017) finding that black patrons were more likely to penalize servers through tipping when dissatisfied with service, and with which found that Black patrons rated their servers less prompt, controlling for objective service cues.…”
Section: Discussionsupporting
confidence: 79%
“…Evidence from polling and research suggests that Black restaurant patrons may experience discrimination in restaurant service. In a 2015 Gallup poll, 20% of Black respondents reported being treated unfairly because of their race in a restaurant, bar, theater, or entertainment venue within the last month (Brewster & Brauer, 2017). As this captures perceived discrimination, a survey study of 200 restaurant servers across 18 restaurants found that 38.1% of the respondents admitted to sometimes varying their service quality by race (Brewster & Rusche, 2012).…”
Section: Literature Reviewmentioning
confidence: 99%
“…We identified 11 studies that collectively represent 15 independent samples 7 comprised of 1,156 and 4,003 Black and White customers, respectively. 8 As shown in Table 1, these studies have analyzed local, regional, and national samples of consumers (see Leodoro & Lynn, 2007) and have employed a variety of different methodologies including server records (Jewell, 2008; Leodoro & Lynn, 2007; Lynn & Thomas-Haysbert, 2003; Noll & Arnold, 2004), customer exit surveys (Brewster & Lynn, 2014; Lynn et al, 2008; Lynn & Thomas-Haysbert, 2003), and telephone/online surveys of consumers (Brewster & Brauer, 2017b; Lynn, 2004a, 2011, 2014; Lynn & Brewster, 2015). The unconditional average differences in Black and White customers’ tipping practices observed in these studies ranged from 1.87 to 7.18 percentage points with a grand mean difference of 3.95 (CI 95% = 2.14, 5.76) percentage points.…”
Section: Resultsmentioning
confidence: 99%
“…Table 2 indicates that most studies have been conducted in the USA, though usually with a focus on one restaurant. Tip size is in the order of 20% to 22% in the exit surveys (Brewster & Lynn, 2014;Whaley et al, 2019), 17.8% to 19.3% in an online survey (Brewster & Brauer, 2017), and 11.97% to 21.07% in a summary of studies on tipping differentials between Black and White customers (Brewster & Nowak, 2019). This confirms that US-tipping levels are high, specifically if compared to the only European study, which identified an average 4.1% gratuity in a restaurant in Switzerland (Fernandez et al, 2016).…”
Section: Pricing System Income and Tip Sizementioning
confidence: 99%
“…For instance, previous studies have measured tip size on the basis of online surveys with hypothetical bill sizes (e.g. Brewster & Brauer, 2017), exit surveys (e.g. Brewster & Lynn, 2014;Whaley et al, 2019), or by using data from point of sale systems (Kim et al, 2017).…”
Section: Pricing System Income and Tip Sizementioning
confidence: 99%